Targeting the MAPK and PI3K pathways in combination with PD1 blockade in melanoma - Deken, Marcel A. (Oncoimmunology, 2016)
Immunotherapy of advanced melanoma with CTLA-4 or PD-1/PD-L1 checkpoint blockade induces in a proportion of patients long durable responses. In contrast, targeting the MAPK-pathway by selective BRAF and MEK inhibitors induces high response rates, but most patients relapse. Combining targeted therapy with immunotherapy is proposed to improve the long-term outcomes of patients. Preclinical data endorsing this hypothesis are accumulating. Inhibition of the PI3K-Akt-mTOR pathway may be a promising treatment option to overcome resistance to MAPK inhibition and for additional combination with immunotherapy. We therefore evaluated to which extent dual targeting of the MAPK and PI3K-Akt-mTOR pathways affects tumor immune infiltrates and whether it synergizes with PD-1 checkpoint blockade in a BRAF(V600E)/PTEN(−/−)-driven melanoma mouse model. Short-term dual BRAF + MEK inhibition enhanced tumor immune infiltration and improved tumor control when combined with PD-1 blockade in a CD8(+) T cell dependent manner. Additional PI3K inhibition did not impair tumor control or immune cell infiltration and functionality. Analysis of on-treatment samples from melanoma patients treated with BRAF or BRAF + MEK inhibitors indicates that inhibitor-mediated T cell infiltration occurred in all patients early after treatment initiation but was less frequent found in on-treatment biopsies beyond day 15. Our findings provide a rationale for clinical testing of short-term BRAF + MEK inhibition in combination with immune checkpoint blockade, currently implemented at our institutes. Additional PI3K inhibition could be an option for BRAF + MEK inhibitor resistant patients that receive targeted therapy in combination with immune checkpoint blockade.